Pangangabit phenomenon from the perspective of the legal wife - Labaclado, Jessa A.; Ojeda, Nova Thirsty N (Tacloban City Jessa A. Labaclado, 2009)
This study investigated the pangangabit phenomenon from the perspective of the legal wife. First it sought to identify the condition of marriage prior to the pangangabit of the husband. Second, it explored the reasons why the husband engaged in pangangabit. And finally, it investigated the motivation of the husband to stay or remain in the extramarital affair. Following a descriptive-qualitative research design, the researchers interviewed ten legal wives with erring husbands in San Miguel, Leyte selected through purposive sampling. Furthermore, the co-triangulation method was utilized to avoid biases in the data by verifying their statements through their children.
Confessions of wives in this study showed that majority of the marriages had been going smoothly before the husband's affair happened. "Going smoothly" from the perspective of the wife meant that the traditional roles of husbands (as providers) and wives (as nurturers) were faithfully performed and there were minimal quarrels and misunderstandings between the couple. One respondent however said that her marriage did not have any strong foundation and lacked love and intimacy from the very beginning. Some couples were also physically separated before and during the time of the pangangabit because of workplace relocation.
This study also found out that from the perspective of the wife, major reasons behind the pangangabit of their husbands are: (1) gratification and excitement they derive from sexual relationships with other women, generally those who are younger than their wife; (2) husband's capacity to provide financial support or sustento to the kabit; (3) accessibility of women willing to be the kabit of the husband either through the husband pursuing the woman, or the woman taking the initiative; (4) physical distance between the couple because of work relocation of either the husband or the wife; and (5) peer influence.
Furthermore, when asked what their husbands related to them as the reason for their pangangabit, their need for sex seemed to be the frequent answer. This is classified into two. For those couples who were physically distant from each other, it is lack of sex due to the absence of their partner; whereas it was sexual variety for those couples who were living together. Majority also reasoned that the youth and beauty of the "other woman" coupled with the affection she showed to them was indeed tempting. Still many explained that the affair was just for leisure.
Another remarkable finding in this study is the large percentage of wives who revealed that they viewed their unfailing trust towards their husband and more so their innocence about their husband's affairs to be the major motivating factor of the pangangabit. Following that the financial capacity of the husband to expend for his extramarital relations.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science